ADVANCED LIQUID CHROMATOGRAPHY TANDEM MASS SPECTROMETRY METHOD FOR SELECTIVE QUANTIFICATION OF NITROSAMINE IMPURITIES WITH PARTS PER BILLION LEVELS IN SACUBITRIL VALSARTAN TABLETS: ENHANCING DRUG SAFETY - GOGADA V PADMAKAR RAO,; DUVVURI SURYAKALA,; MEKA LINGAM,; BAVISETTI LAKSHMI, (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Nitrosamine impurities may be present at low levels in various products to which people are routinely exposed. Regulatory agencies have determined that nitrosamines can form in any drug substance or drug product in which secondary, tertiary, or quaternary amines were present along with nitrosating agents. The objective of this current work is to develop a sensitive and robust method that outputs a trace-level quantification and simultaneous detection of the nitrosamine impurities (N-Nitrosodimethylamine [NDMA] and N-Nitrosodiethylamine [NDEA]) in the drug product of Sacubitril valsartan using a triple quadrupole liquid chromatography tandem mass spectrometry (LC-MS/MS) system to ensure the patient safety and compliance with regulatory expectations. Methods: A liquid chromatograph system with a triple quadrapole mass spectrometry detector (Shimadzu LC-MS/MS). During the development of a method, the conditions for chromatographic separation with Shim-pack GST C8 Column (150 mm*4.6 mm, 3.0 μm) elution with formic acid and methanol as a mobile phase (separation achieved with gradient program with run time of 25 min) using gradient elution with formic acid and methanol as a mobile phase. Peak shape and area response optimized with diluent methanol and water in the ratio of 80:20 v/v with an injection volume of 50 μL. For ionization, atmospheric pressure chemical ionization mode with Multiple Reaction Monitoring (MRM) transition has been used for the quantification of NDMA and NDEA with a program run time of 25 min. The method utilizes a flow rate of 0.500 mL/min and at a column temperature of 35°C±0.5°C, sample temperature of 15°C±0.5°C. The resulting method was validated for specificity, linearity, limit of quantification (LOQ), limit of detection (LOD), accuracy, and precision. Results: The method was specific as there is no interference was observed at the retention time of each analyte, and the results were well within the limits. The LOD and LOQ of Sacubitril and valsartan for NDMA and NDEA were reported with 7 parts per billion (ppb) and 21.2 ppb, and 1.9 ppb and 5.8 ppb levels, respectively. The Linearity curve was generated by plotting the area ratios against the drug concentration and reported the R2 values for NDMA, NDEA, is 0.997 and 0.999, respectively, and the method can quantify NDEA linear from 10 ppb to 120 ppb and NDMA linear from 20 ppb to 420 ppb. Recovery results (NDEA) reported for LOQ are 117.24%, 50% is 115.69%, 100% is 109.58, and 200% is 108.72, and recovery results (NDMA) reported for LOQ are 110.27%, 50% is 107.84%, 100% is 102.58, and 200% is 94.83 with % relative standard deviation <15.0%. Conclusion: Based on the results, it can be concluded that the method is reliable for the detection and quantification of NDMA and NDEA nitrosamine impurities in Sacubitril valsartan tablets.